Growth and Yield of Cauliflower (Brassica Oleracea. L.) as an Effect of Water Supply and the Dosages of Rice Straw Mulch - Noertjahyani; Komariah, Ai; Nurlenawati , Netti (Asian Journal of Agriculture and Rural Development, 2019)
Limited available water, especially in dry land, causes decreasing production of vegetable plants. Cauliflower originates from subtropical regions which require water. Mulching can manage water to a limited extent. An experiment was carried out in the lowlands to find out whether cauliflower cultivar Orient hybrid could grow in an environment with water available under optimal conditions combined with the use of rice straw mulch. The experimental results show that the Orient hybrid of cauliflower is a lowland plant that can provide the same (marketable curd) yield even with the water conditions below the field capacity (75% FC). The use of rice straw mulch doses of 5-10 t ha-1 can help maintain water available for plants. The Orient cultivar hybrid is a lowland cauliflower sufficiently tolerant to lack of water.